Perancangan Aplikasi Pempelajaran Dalam Mengenal Warna Dengan 2 Bahasa ( Indonesia Dan Inggris) Berbasis Android Menggunakan Metode Prototype Di SDN Sawangan 6 - Veny F, Riska; Ditania, Nazua; Novanti Eno, Maria; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
Technological advances have made a significant contribution to supporting education, particularly at the elementary school level. One of the challenges faced in the learning process for young children is how to convey color recognition material in an engaging and effective manner. This study aims to develop an Android-based educational application that introduces colors to young children in two languages, namely Indonesian and English. The development of the application was carried out using was conducted using the Prototype method to ensure the application design can be continuously improved based on user feedback. The application includes learning features, games, and interactive quizzes aimed at stimulating children's cognitive abilities through visual displays and sound. Based on initial testing, the application has proven effective in increasing children's learning enthusiasm and helping them understand color concepts and vocabulary more more easily in two languages. With its enjoyable and flexible presentation, this application has the potential to become an innovative learning medium for young children.